Incidence of diabetic foot ulcer in Japanese patients with type 2 diabetes mellitus: The Fukuoka diabetes registry. (March 2018) - Iwase, Masanori; Fujii, Hiroki; Nakamura, Udai; Ohkuma, Toshiaki; Ide, Hitoshi; Jodai-Kitamura, Tamaki; Sumi, Akiko; Komorita, Yuji; Yoshinari, Masahito; Kitazono, Takanari
Abstract: Aims: Although diabetic foot ulcer (DFU) is a serious diabetic complication, there have been no large-scale epidemiological studies of DFU in Japan. We prospectively investigated the incidences of DFU and limb amputation, the risk for developing DFU, and mortality in Japanese patients with type 2 diabetes. Methods: We followed 4870 participants (mean age, 65 years) with type 2 diabetes attending an outpatient diabetes clinic for a median of 5.3 years (follow-up rate, 97.7%). The primary outcome was the development of DFU. Results: During the follow-up period, DFU occurred in 74 participants (incidence rate, 2.9/1000 person-years) and limb amputation in 12 (incidence rate, 0.47/1000 person-years). DFU recurrence was observed in 21.4% of participants with history of DFU. History of DFU, chronic kidney disease (estimated glomerular filtration rate <60 mL/min/1.73 m 2 ), depressive symptoms, and poor glycemic control were significant risk factors for developing DFU. Survival was significantly lower in participants with DFU and/or history of DFU compared with those without (5-year survival rates: with DFU, 87.7%, without DFU, 95.3%; P < .0001). The hazard ratio for death was 1.80 (95% confidence interval, 1.13–2.73, P = .014) in those with DFU and/or history of DFU in a multi-adjusted model. The most common cause of death was cardiovascular disease among participants with DFU, whereas it was malignant neoplasm among those without. Conclusions: Incidences of DFU and limb amputation were 0.3% and 0.05% per year in this Japanese cohort, respectively. Mortality significantly increased approximately 2-fold in those with DFU and/or history of DFU compared with those without.